2003
DOI: 10.1002/eji.200324273
|View full text |Cite
|
Sign up to set email alerts
|

Death of peripheral CD8+ T cells in the absence of MHC class I is Fas‐dependent and not blocked by Bcl‐xL

Abstract: Productive immune responses require an appropriate environment to support peripheral CD8 + T cell survival. Although host MHC class I molecules appear to be required for this process, the cellular and molecular requirements have not been comprehensively studied. Using adoptive transfer of 2C/recombinase-activating gene-2 (RAG-2) -/-TCR-transgenic T cells, we found that the survival of both naive and effector CD8 + T cells was dependent upon host expression of the same MHC class I alleles that supported thymic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
2
18
1
Order By: Relevance
“…S1C). This is in sharp contrast to recently reported results for CD8 T cells, which can survive by means of contact with MHCI expressed by either hematopoietic or stromal compartments (31), and can be rendered tolerant by specific antigen presented by radioresistant LN stroma (32).…”
Section: Discussioncontrasting
confidence: 99%
“…S1C). This is in sharp contrast to recently reported results for CD8 T cells, which can survive by means of contact with MHCI expressed by either hematopoietic or stromal compartments (31), and can be rendered tolerant by specific antigen presented by radioresistant LN stroma (32).…”
Section: Discussioncontrasting
confidence: 99%
“…The requirement for MHC in survival of naïve CD8 T cells has since been confirmed in both transgenic and polyclonal T cells (see for example (23,24)). An intriguing observation is that CD8 T cells do not die immediately after transfer to MHCdeficient environments.…”
Section: Self-mhc and Cd8 T Cell Homeostasismentioning
confidence: 96%
“…An intriguing observation is that CD8 T cells do not die immediately after transfer to MHCdeficient environments. Rather, they survive and can respond to accessory cell signals for at least one week (23), and their eventual death is dependent on expression of the death factor protein Fas and its interaction with Fas ligand (FasL) (24). Rocha et al showed that survival of naïve CD8 cells was not only dependent on MHC expression, but also required the right MHC-restricting element (25).…”
Section: Self-mhc and Cd8 T Cell Homeostasismentioning
confidence: 99%
“…Tonic TCR engagement is generated by the interaction of the TCR with weakly reactive self-peptides (3). Survival of quiescent CD8 T cells requires MHC class I-TCR engagement, which is indicated by dwindling numbers of naïve CD8 T cells after transfer into MHC class I-deficient mice (4,5). In addition, long-term (but not short-term) survival of CD4 T cells requires the presence of MHC class II (6).…”
mentioning
confidence: 99%